Silver nitrate enhances antibacterial effect of colistin against intrinsic colistin resistant Edwardsiella piscicida - Shi, Yangbin; Mei, Luyu; Laghari, Zubair Ahmed; Tu, Caiyi; Pan, Yajing; Zhang, He; Lou, Yongliang; Lu, Jinfang (Frontiers in Veterinary Science, 2025)
Edwardsiella piscicida (E. piscicida) has been recognized as an important bacterial pathogen affecting fish, and it is also intrinsically resistant to colistin. E. piscicida infects many species of cultured fish and aquatic animals, posing a significant threat to the global aquaculture industry and ecological systems. Therefore, alternative treatment strategies are urgently required to combat E. piscicida infections effectively. In this study, the combination of silver nitrate and colistin demonstrated strong bactericidal activity against both in vitro and in vivo. Silver nitrate significantly reduced the minimum inhibitory concentration (MIC) of E. piscicida and enhanced the antibacterial effect of colistin against E. piscicida. Moreover, the combination effectively eliminated E. piscicida in zebrafish, and significantly increased their survival. Mechanistic analysis revealed that silver nitrate and colistin disrupted bacterial redox homeostasis by targeting the thioredoxin (Trx) system, inducing the over-production of reactive oxygen species (ROS) and malondialdehyde (MDA), suppressing the activities of superoxide dismutase (SOD) and catalase (CAT), and depleting glutathione (GSH), resulting in severe oxidative stress. In addition, silver nitrate strongly enhanced the membrane damage ability of colistin, increased membrane permeability, and decreased membrane potential with obvious morphological damages. The silver nitrate–colistin combination strikingly attenuated the essential pathways involving in drug efflux, cationic antimicrobial peptides resistance (CAMP), and mechanisms related to infection and virulence. These results highlight the potential of the combination of silver nitrate and colistin as an effective treatment strategy against intrinsically colistin-resistant E. piscicida.